Face Mask Wearing Behaviors, Depressive Symptoms, and Health Beliefs Among Older People During the COVID-19 Pandemic - Kwan, Rick Yiu Cho; Lee, Paul Hong; Cheung, Daphne Sze Ki; Lam, Simon Ching (Frontiers in Medicine, 2021)
The COVID-19 pandemic has affected more than 100 countries. Despite the global shortage of face masks, the public has adopted universal mask wearing as a preventive measure in many Asian countries. The COVID-19 mortality rate is higher among older people, who may find that wearing a face mask protects their physical health but jeopardizes their mental health. This study aimed to explore the associations between depressive symptoms, health beliefs, and face mask wearing behaviors among older people. By means of an online survey conducted between March and April 2020, we assessed depressive symptoms, health beliefs regarding COVID-19, and face mask use and reuse among community-dwelling older people. General linear models were employed to explore the associations among these variables. Of the 355 valid participants, 25.6% experienced depressive symptoms. Health beliefs regarding the perceived severity of disease (p = 0.001) and perceived efficacy of practicing preventive measures (p = 0.005) were positively associated with face mask use. Those who reused face masks (p = 0.008) had a stronger belief in disease severity (p < 0.001), had poorer cues to preventive measures (p = 0.002), and were more likely to experience depressive symptoms. Mask reuse was significantly associated with depression only among those who perceived the disease as serious (p = 0.025) and those who had poorer cues to preventive measures (p = 0.004). In conclusion, health beliefs regarding perceived severity and efficacy contributed to more frequent face mask use, which was unrelated to depressive symptoms. Older people who had a stronger belief in disease severity had less adequate cues to preventive measures and reused face masks experienced greater depressive symptoms. A moderation effect of health beliefs (i.e., disease severity and cues to preventive measures) on face mask reuse and depression was observed.